Tras las huellas de la mujer de Job, la Sophía y las narrativas de lo femenino en el libro de Job (2,9-10; 28) = In the Footsteps of Job’s Wife, Sophia and Narratives of the Feminine in the Book of Job (2,9-10; 28) - Cabrera Piñango, Rebeca (Revista de interpretação bíblica latino-americana, 2023)
This article wants to be a contribution to the study of the book of Job from the female perspective; is a destabilizing text that questions the ideas rooted in the jewish imaginary, about the “theology of retribution,” where Job presents himself as a character whose faith is purifying over time and goes from asking for a mediator to believing in a liberating God in the midst of a constant attitude of complaint. In this context, Job’s wife appears in contrast to her husband, scholars question her, forgetting that she, except for her illness, suffered the same losses as Job. Doesn’t she have any reason? We will try to follow in her footsteps and seek wisdom in the words of women.